Rebozo Technique Application and Back Pain Reduction to Improve Reproductive Health in Pregnant Women - Yetti Atiyah; Elvi Sepriani (Benih : Journal of Midwifery, 2026)
Pregnancy-related hormonal and biomechanical changes may reduce pelvic and back stability and contribute to back pain, particularly in the third trimester. The Rebozo technique, which uses a shawl to provide gentle rocking or pressure around the pelvis, is a non-pharmacological approach intended to reduce discomfort and support maternal well-being. This study aimed to determine the relationship between the application of the Rebozo technique and reduced back pain levels to improve reproductive health in pregnant women. A quantitative analytical study with a cross-sectional approach was conducted at the Juliana Dalimunthe Clinic from April to June 2026. Thirty-five third-trimester pregnant women with back pain were selected using accidental sampling. Data were collected using a questionnaire and analyzed using the chi-square test at a 95% confidence level (alpha = 0.05). Thirty respondents (86%) applied the Rebozo technique. The association between Rebozo application and reduced back pain was statistically significant (p = 0.001). The Rebozo technique may be used as a complementary, non-pharmacological option to help pregnant women manage third-trimester back pain and support reproductive health.